Flavonoides totais, atividade antioxidante e variação sazonal da composição química do óleo essencial de alecrim-pimenta (Lippia origanoides Kunth.) - Luciana Mendes de Souza (2015)
Lippia origanoides Kunth. is a shrub originating from the northeast of South America, used as a condiment and for medicinal purposes. The essential oil produced by this species presents antimicrobial activity and contains the following chemical markers: thymol and carvacrol. However, it is reported that this species presents variation in its chemical composition, therefore it is classified as chemotypes. Besides the essential oil, there are flavonoids, which act as antioxidants. The objective of this study was to determine the flavonoid content and the antioxidant activity, in addition to studying the seasonal variation in the chemical composition of the L. origanoides essential oil. The first study was conducted with a natural population of L. origanoides, with 30 individuals collected both in the dry season and the rainy season. The second study was conducted with accessions from the collection of germplasm bank of L. origanoides in vivo at the Institute of Agricultural Sciences of the Federal University of Minas Gerais (ICA-UFMG). Monthly collections of eight accessions were held during one year. The essential oil was extracted by hydrodistillation and analyzed by gas chromatography-mass spectrometry (GC-MS). Multivariate analysis was used to evaluate the genetic divergence among the plants of the natural population. The content of flavonoids in the germplasm bank accessions was determined by aluminum chloride method (AlCl3) and expressed in milligrams of rutin equivalent (mg RE g -1). The evaluation of antioxidant activity was conducted by radical DPPH sequestration method, the effective concentration (EC50) was calculated with the equations obtained from the quadratic regression, and the index of antioxidant activity was calculated using the concentration of DPPH divided by EC50. The results of flavonoids and antioxidant activity were submitted to analysis of variance and the averages were compared by Tukey test. The Pearson correlation coefficient was used to evaluate the relationship between flavonoids and antioxidant activity. The yield of essential oil in the natural population was higher in the rainy season. Carvacrol was the major compound in most plants studied in both seasons. Tocher grouping revealed five distinct groups. Group 1 contained 26 of the 30 plants studied in both dry and rainy seasons, indicating that the time of the year evaluated did not 16 interfere significantly in the essential oil composition. Only four plants were divided into different groups, i.e., there were important differences between the two seasons for these plants. The yield of essential oil in the germplasm bank accessions ranged from 2.20% to 4.18%. Five accessions were considered stable regarding the chemical composition, since the major compounds did not vary during the year. In these accesses, carvacrol was the major compound. Three accessions were considered unstable, since they presented different major compounds during the year. For these accessions, the major compounds were eucalyptol, carveol and -pinene. The average amount of flavonoids in the accesses from the germplasm bank was 254.55 mg RE g -1 and its extracts showed moderate antioxidant activity. The total flavonoid had a positive correlation (r = 0.83) with antioxidant activity.